Diplomasi Bencana India terhadap Nepal pada Tahun 2015 - Wahyu Rozzaqi Ginanjar (Global Political Studies Journal, 2020)
Disaster is an inevitable thing for all human beings. Very often disasters occur in certain political contexts. Disaster diplomacy is an effort of a country to improve the quality of diplomacy with other countries by utilizing disasters to open new opportunities in terms of diplomatic context. This was done by India following the massive earthquake in Nepal in 2015. India has very specific concerns related to domestic conditions in Nepal. India's concern over Nepal's domestic conditions is generally related to the issue of the Madhes movement in the Tarai region. This became a concern to India because the Madhes movement has created instability in the Tarai region that has disrupted India's economic agenda in the South Asian region. Based on this, India then encouraged a number of diplomatic efforts in the context of creating reconciliation between the Madhes and Pahadi groups who were in conflict in Nepal. The earthquake in Nepal was used by India as a catalyst to support diplomatic efforts to create a more stable domestic condition in Nepal. This article then tries to discuss the form of disaster diplomacy carried out by India towards Nepal. Using the concept of disaster diplomacy from Ian Kelman, this article illustrates India's efforts to utilize the Nepal earthquake disaster as a catalyst to improve the quality of diplomacy towards Nepal as a whole in relation to the Madhes movement. This article discovers the fact that Indian disaster diplomacy met a contrary to what was expected outcome, following the growing conflict between Madhes and Pahadi groups after the 2015 Nepal earthquake.